Sexual Violence In Schools: The Case Of The Djibo Municipal Secondary School Sounkalo In Bouake - AKPOUE Adjoua Marie Charlotte; N’GUESSAN Kassi Sinaï (International Journal of Scientific Research and Innovative Studies, 2025)
The objective of this research is to analyse the explanatory factors of the persistence of sexual violence in schools at the Djibo Sounkalo high school in Bouake. Sexual violence in schools is a problem. This violence can take different forms, ranging from sexual harassment to sexual assault, often affecting students, especially young girls. The methodology used is based on a qualitative approach. The techniques used are direct observation, documentary research and semi-structured interviews. The results obtained show, among other things, that the factors that promote this violence are often the style of clothing worn by young girls, lack of sex education and drug use on the one hand, and on the other hand, this study has indicated certain consequences such as absenteeism, school dropout, trauma, etc. Finally, we identified prevention strategies and made proposals for recommendations. Keywords: Harassment, Sexual violence, Stigmatisation, Protection policy, Victim. Received Date: July 19, 2025 Accepted Date: August 11, 2025 Published Date: August 30, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/493